DNA barcoding in pencilfishes (lebiasinidae: nannostomus) reveals cryptic diversity across the brazilian Amazon - Benzaquem, Denise Correa; Oliveira, Claudio [UNESP]; Batista, Jaqueline da Silva; Zuanon, Jansen; Rebelo Porto, Jorge Ivan (Public Library Science, 2015)
Nannostomus is comprised of 20 species. Popularly known as pencilfishes the vast majority of these species lives in the flooded forests of the Amazon basin and are popular in the ornamental trade. Among the lebiasinids, it is the only genus to have undergone more than one taxonomic revision. Even so, it still possesses poorly defined species. Here, we report the results of an application of DNA barcoding to the identification of pencilfishes and highlight the deeply divergent clades within four nominal species. We surveyed the sequence variation in the mtDNA cytochrome c oxidase subunit I gene among 110 individuals representing 14 nominal species that were collected from several rivers along the Amazon basin. The mean Kimura-2-parameter distances within species and genus were 2% and 19,0%, respectively. The deep lineage divergences detected in N. digrammus, N. trifasciatus, N. unifasciatus and N. eques suggest the existence of hidden diversity in Nannostomus species. For N. digrammus and N. trifasciatus, in particular, the estimated divergences in some lineages were so high that doubt about their conspecific status is raised.